Cold Promoted Activation of Factor VII - GJØNNÆSS, H (Thrombosis and Haemostasis, 1973)
Spontaneous cold promoted activation of factor VII was independent of the fibrinolytic activity of plasma and caused no activation of plasminogen.After the spontaneous cold activation a highly significant increase in the proteolytic capacity was observed which was not seen after induced cold activation.Cold activation induced with known prekallikrein activators (EACA, kaolin, Li- quoid) or with a semipurified plasma kallikrein preparation was independent of the fibrinolytic activity of plasma and caused no change in this.Cold activation induced with urokinase and with streptokinase was probably mediated by plasmin. The urokinase induced activation of plasminogen was independent of factor XII, whereas this factor was a prerequisite for the cold activation of factor VII.The urokinase induced cold activation of factor VII correlated with increased TAME - esterolytic activity and an 80 per cent decrease of the kininogen concentration, indicating activation of the plasma kallikrein system.